Conductive composite material

By modifying the hydrogen group on the surface of MXENE and forming hydrogen bonds with the polymer material, the problem of taking into account the conductivity and strength of MXENE and polymer composite materials is solved, and a composite with high conductivity and high strength is achieved.

JP7626138B2Active Publication Date: 2025-02-04MURATA MFG CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2022541533
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-08-03
Filing Date
2021-08-02
Publication Date
2025-02-04
Estimated Expiration
2041-08-02

AI Technical Summary

Technical Problem

The existing MXENE and polymer composite materials are difficult to balance between maintaining high conductivity and high strength, and there is a problem of significant decrease in conductivity or insufficient strength.

Method used

The composite of a specific layered material MXENE and polymer material is used to improve conductivity and strength by modifying hydrogen bonds between the hydrogen groups and the polymer material on the surface of MXENE.

Benefits of technology

The high conductivity and high strength are achieved, with the conductivity up to 280S/cm or higher, and the strength is also improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007626138000004
    Figure 0007626138000004
  • Figure 0007626138000005
    Figure 0007626138000005
  • Figure 0007626138000006
    Figure 0007626138000006
Patent Text Reader

Abstract

Provided is a conductive composite material that is formed from a polymer material and a MXene and that achieves both high conductivity and high strength. The conductive composite material includes a polymer material and particles of a layered material including at least one layer. The layer includes: a layer body represented by formula MmXn (in the formula, M represents at least one metal in group 3, 4, 5, 6, or 7, X represents a carbon atom, a nitrogen atom, or a combination thereof, n is 1-4, m is more than n but not more than 5); and a modification or a terminal T (T represents at least one selected from the group consisting of a hydroxyl group, a fluorine atom, a chlorine atom, an oxygen atom, and a hydrogen atom) existing on the surface of the layer body. The polymer material has, as a hydrogen acceptor, at least one selected from the group consisting of a fluorine atom, a chlorine atom, an oxygen atom, and a nitrogen atom, and has, as a hydrogen donor, a hydroxyl group and / or a secondary amino group. The proportion of particles of the layered material is more than 19 vol% but not more than 95 vol%.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an electrically conductive composite material. [Background technology]

[0002] In recent years, MXene has been attracting attention as a new material having electrical conductivity. MXene is a type of so-called two-dimensional material, and as described below, it is a layered material having the form of one or more layers. In general, MXene has the form of particles of such layered material (which may include powder, flakes, nanosheets, etc.).

[0003] To date, composite materials of the above-mentioned MXene and polymers have been produced in order to improve strength, flexibility, etc. For example, Non-Patent Document 1 describes Ti as the above-mentioned MXene. 3 C 2 T x It has been shown that by forming a composite film of Ti and polyvinyl alcohol (PVA), it is possible to ensure flexibility and mechanical strength while maintaining electrical conductivity. 3 C 2 T x and sodium alginate (SA) composite films are shown.

[0004] In Non-Patent Document 3, Ti was used as the MXene in order to ensure electrical conductivity as well as EMI shielding effect. 3 C 2 T x In Non-Patent Document 3, the EMI shielding nanocomposite containing up to 15 mass% of Ti and epoxy is shown, and the Ti nanocomposite is annealed without producing by-products. 3 C 2 T x It has been shown that by partially removing the polar groups on the surface of , it is possible to obtain relatively high electrical conductivity, excellent EMI shielding effectiveness (SE), and suitable hardness.

[0005] Non-Patent Document 4 reports on the use of Ti in a wax matrix as an electromagnetic (EM) absorbing and shielding composite material. 3 C 2 The material in the presence of MXene is shown after annealing.

[0006] Non-Patent Document 5 shows a composite material in which polyurethane (PU) is filled with two-dimensional MXene by the emulsion method, and also shows that the yield stress, tensile strength, and hardness of polyurethane are increased by adding 0.5 mass% of MXene.

[0007] In Non-Patent Document 6, a flame-retardant material using thermoplastic polyurethane (TPU) is reported, which is Ti modified with cetyltrimethylammonium bromide (CTAB) and tetrabutylphosphine chloride (TBPC). 3 C 2 A composite of ultrathin nanosheets of (MXene) and polyurethane is shown. [Prior art documents] [Non-patent literature]

[0008] [Non-Patent Document 1] Zheng Ling, et al., “Flexible and conductive MXene films and nanocomposites with high capacitance”, Proceedings of the National Academy of Sciences,2014, vol.11, pp.16676-16681 [Non-Patent Document 2] Faisal Shahzad, et al., “Electromagnetic interference shielding with 2D transition metal carbides (MXenes)”, Science, 2016, vol.353, pp.1137-1140 [Non-Patent Document 3] Lei Wang, et al., “Fabrication on the annealed Ti3C2Tx MXene / Epoxy nanocomposites for electromagnetic interference shielding application”, Composites Part B, 2019, vol.171, pp.111-118 [Non-Patent Document 4] Meikang Han, et al., “Ti3C2 MXenes with Modified Surface for High-Performance Electromagnetic Absorption and Shielding in the X-Band”, ACS Applied Materials Interfaces, 2016, vol.8, pp.21011-21019 [Non-Patent Document 5] Weiqiang Zhi, et al., “Study of MXene-filled polyurethane nanocomposites prepared via an emulsion method”, Composites Science and Technology, 2018, vol.168, pp.404-411 [Non-Patent Document 6] Bin Yu, et al., “Interface decoration of exfoliated MXene ultra-thin nanosheets for fire and smoke suppressions of thermoplastic polyurethane elastomer”, Journal of Hazardous Materials, 2019, vol.374, pp.110-119 Summary of the Invention [Problem to be solved by the invention]

[0009] Among the MXene-polymer complexes shown in Non-Patent Documents 1 to 6, the Ti 3 C 2 T x The composite film of Ti and PVA 3 C 2 T x The Ti content is high at 90 mass%, but pure Ti 3 C 2 T x The conductivity is significantly reduced to less than one-tenth of that of the film.

[0010] The maximum Ti content of 15 mass% shown in Non-Patent Document 3 3 C 2 T x The EMI shielding nanocomposite of Ti and epoxy is unlikely to deform when a load is applied and has an appropriate hardness. However, the maximum electrical conductivity is 0.38 S / cm, which is significantly lower than the electrical conductivity of a pure MXene film, which is several thousand S / cm. 3 C 2 Although composite materials containing (MXene) have excellent electromagnetic (EM) absorption capabilities, their electrical conductivity is at most 0.001 S / cm, which is significantly lower than that of pure MXene films.

[0011] Although the composite materials of MXene and polyurethane described in Non-Patent Document 5 and Non-Patent Document 6 exhibit high yield stress, tensile strength, and hardness, the composite materials are presumed to exhibit insulating properties and have extremely low electrical conductivity.

[0012] On the other hand, the composite film of MXene and sodium alginate (SA) in Non-Patent Document 2 had a maximum of 2963 S / cm (Ti 3 C 2 T x 90% by mass), but the strength is considered to be low.

[0013] As described above, currently available composites of MXene and polymers do not achieve both high electrical conductivity and high strength. The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a composite material of MXene and a polymer material that achieves both high electrical conductivity and high strength. [Means for solving the problem]

[0014] According to one aspect of the present invention, there is provided a conductive composite material comprising particles of a layered material comprising one or more layers and a polymeric material, the particles comprising: The layer comprises a compound having the following formula: M m X n (wherein M is at least one Group 3, 4, 5, 6, or 7 metal; X is a carbon atom, a nitrogen atom, or a combination thereof; n is 1 or more and 4 or less, m is greater than n and less than or equal to 5) and a modification or termination T (T is at least one selected from the group consisting of a hydroxyl group, a fluorine atom, a chlorine atom, an oxygen atom, and a hydrogen atom) present on the surface of the layer body, The polymeric material comprises: at least one hydrogen acceptor selected from the group consisting of a fluorine atom, a chlorine atom, an oxygen atom, and a nitrogen atom; and having a hydroxyl group and / or a secondary amino group as a hydrogen donor; An electrically conductive composite material is provided, wherein the proportion of particles of the layered material is greater than 19% by volume and not greater than 95% by volume. Effect of the Invention

[0015] According to the present invention, a conductive composite material comprises particles of a predetermined layered material (also referred to in this specification as "MXene") and a polymer material, the polymer material having at least one selected from the group consisting of fluorine atoms, chlorine atoms, oxygen atoms and nitrogen atoms as a hydrogen acceptor, and a hydroxyl group and / or a secondary amino group as a hydrogen donor, and the proportion of the particles of the layered material is more than 19 volume % and 95 volume % or less, thereby providing a composite material that contains MXene and can achieve both high conductivity and high strength. [Brief description of the drawings]

[0016] [Figure 1] FIG. 1 is a schematic cross-sectional view showing a conductive composite material according to one embodiment of the present invention. [Diagram 2] FIG. 1 is a schematic cross-sectional view showing MXene, a layered material that can be used in a conductive composite material in one embodiment of the present invention. [Diagram 3] FIG. 1 is a schematic diagram illustrating the presence or absence of hydrogen bonds in a conductive composite material according to one embodiment of the present invention and a conventional embodiment. [Figure 4] 1 is a graph showing the relationship between the MXene content and electrical conductivity of each conductive composite material. [Diagram 5] 1 is a graph showing the relationship between the MXene content in each conductive composite material and the ratio to the electrical conductivity of MXene alone. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0017] Hereinafter, a conductive composite material according to one embodiment of the present invention will be described in detail, but the conductive composite material of the present invention is not limited to this embodiment.

[0018] 1, the conductive composite material 20 of this embodiment includes particles 10 of a predetermined layered material and a polymer material 11. The polymer material 11 has a hydrogen acceptor and a hydrogen donor, which will be described later, and thus hydrogen bonds are formed between the layered material particles 10 and the polymer material 11, increasing the affinity between the layered material particles 10 and the polymer material 11, and increasing the electrical conductivity.

[0019] In this embodiment, the particles of the predetermined layered material are MXene (particles), and are defined as follows. A particle of layered material comprising one or more layers, the layers being represented by the following formula: M m X n where M is at least one group 3, 4, 5, 6, 7 metal and may include at least one selected from the group consisting of so-called early transition metals, such as Sc, Ti, Zr, Hf, V, Nb, Ta, Cr, Mo and Mn; X is a carbon atom, a nitrogen atom, or a combination thereof; n is 1 to 4, m is greater than n and less than or equal to 5) and a modification or termination T (T is at least one selected from the group consisting of a hydroxyl group, a fluorine atom, a chlorine atom, an oxygen atom, and a hydrogen atom) present on a surface of the layer body (more specifically, on at least one of the two opposing surfaces of the layer body). m X n T x ", where x is any number, and z or s may be used instead of x in the past. Typically, n can be 1, 2, 3 or 4.

[0020] In the above formula for MXene, M is preferably at least one selected from the group consisting of Ti, Zr, Hf, V, Nb, Ta, Cr, Mo, and Mn, and more preferably at least one selected from the group consisting of Ti, V, Cr, and Mo.

[0021] In the above formula of MXene, it is more preferable that M is Ti and X is carbon atom or carbon atom and nitrogen atom. 3 C 2 , Ti 3 CN, and Ti 2 More preferably, at least one selected from the group consisting of Ti 3 C 2 T x (x is any number) is preferred.

[0022] Such MXenes can be synthesized by selectively etching (removing and optionally phase-separating) the A atoms (and optionally some of the M atoms) from the MAX phase. The MAX phase has the following formula: M m AX n (wherein M, X, n and m are as defined above, and A is at least one Group 12, 13, 14, 15, 16 element, usually a Group A element, typically Group IIIA and Group IVA, and more particularly may include at least one element selected from the group consisting of Al, Ga, In, Tl, Si, Ge, Sn, Pb, P, As, S and Cd, and is preferably Al). and M m X n (each X may have a crystal lattice in which it is located in the octahedral array of M) between which a layer composed of A atoms is located. In the MAX phase, typically when m=n+1, one layer of X atoms is arranged between each of the n+1 layers of M atoms (collectively referred to as "M m X n and a layer of A atoms (also referred to as an "A atom layer") arranged as a layer next to the n+1th layer of M atoms, but is not limited thereto.

[0023] In the process of preparing MXene, A atoms (and possibly some of the M atoms) are selectively etched (removed and possibly delaminated) from the MAX phase, thereby removing a layer of A atoms (and possibly some of the M atoms) and exposing the M m X n The surface of the layer is modified with hydroxyl groups, fluorine atoms, chlorine atoms, oxygen atoms, hydrogen atoms, etc. present in the etching solution (usually, an aqueous solution of fluorine-containing acid is used, but is not limited to this) to terminate the surface. - The etching may be carried out using an etching solution containing the above, for example, a method using a mixture of lithium fluoride and hydrochloric acid, or a method using hydrofluoric acid. After that, layer separation of MXene (delamination, separation of multi-layered MXene into single-layered MXene) may be promoted by any appropriate post-treatment (for example, ultrasonic treatment, handshake, etc.). For example, when obtaining single-layered or few-layered MXene described later, it is preferable to carry out the following method. That is, the etched product obtained by the above etching is washed with water, and then intercalation is carried out. As the intercalation compound used for intercalation, for example, an alkali metal compound or an alkaline earth metal compound is preferable, and Li-containing compound is more preferable. The specific method of intercalation is not particularly limited, and for example, the intercalation compound may be mixed with the water medium clay obtained after the above water washing, and may be stirred or left to stand. Next, delamination is carried out, which includes stirring the treated product obtained by the above intercalation in a liquid such as water. When obtaining single-layered or few-layered MXene, it is preferable not to carry out ultrasonic treatment as delamination. After delamination, single- or few-layered MXene can be obtained as particles of layered material by washing with water.

[0024] MXene is a compound represented by the above formula: m X n However, it is known that it can be expressed as follows: Sc 2 C, Ti 2 C, Ti 2 N, Zr 2 C, Zr2 N、Hf 2 C、Hf 2 N、V 2 C、V 2 N、Nb 2 C、Ta 2 C、Cr 2 C、Cr 2 N、Mo 2 C、Mo 1.3 C、Cr 1.3 C、(Ti,V) 2 C、(Ti,Nb) 2 C、W 2 C、W 1.3 C、Mo 2 N、Nb 1.3 C、Mo 1.3 Y 0.6 C(1.3 and 0.6 are the same as 1.3(=4 / 3) and 0.6(=2 / 3)). The 3 C 2 ,The 3 N 2 ,The 3 (CN)、Zr 3 C 2 、(Ti,V) 3 C 2 ,(The 2 Nb)C 2 ,(The 2 Ta)C 2 ,(The 2 Mn)C 2 、Hf 3 C 2 、(Hf 2 V)C 2 、(Hf 2 Mn)C 2 、(V 2 Ti)C 2 、(Cr 2 Ti)C 2 、(Cr 2 V)C 2 、(Cr 2 Nb)C 2 、(Cr 2 Ta)C 2 、(Mo 2 Sc)C 2 、(Mo 2 Ti)C 2 、(Mo 2Zr)C 2 、(Mo 2 Hf)C 2 、(Mo 2 V)C 2 、(Mo 2 Nb)C 2 、(Mo 2 Ta)C 2 、(W 2 Ti)C 2 、(W 2 Zr)C 2 、(W 2 Hf)C 2 、 Ti 4 N 3 、V 4 C 3 、Nb 4 C 3 、Ta 4 C 3 、(Ti,Nb) 4 C 3 、(Nb,Zr) 4 C 3 、(Ti 2 Nb 2 )C 3 、(Ti 2 Ta 2 )C 3 、(V 2 Ti 2 )C 3 、(V 2 Nb 2 )C 3 、(V 2 Ta 2 )C 3 、(Nb 2 Ta 2 )C 3 、(Cr 2 Ti 2 )C 3 、(Cr 2 V 2 )C 3 、(Cr 2 Nb 2 )C 3 、(Cr 2 Ta 2 )C 3 、(Mo 2 Ti 2 )C 3 、(Mo 2 Zr 2 )C3 , (Mo 2 Hf 2 ) C 3 , (Mo 2 V 2 ) C 3 , (Mo 2 Nb 2 ) C 3 , (Mo 2 Ta 2 ) C 3 , (W 2 Ti 2 ) C 3 , (W 2 Zr 2 ) C 3 , (W 2 Hf 2 ) C 3 , (Mo 2.7 V 1.3 ) C 3 (In the above formula, "2.7" and "1.3" mean approximately 2.7 (= 8 / 3) and approximately 1.3 (= 4 / 3), respectively.)

[0025] Typically, in the above formula, M can be titanium or vanadium, and X can be a carbon atom or a nitrogen atom. For example, the MAX phase is 3 AlC 2 and MXene is Ti 3 C 2 T x (In other words, M is Ti, X is C, n is 2, and m is 3).

[0026] In the present invention, MXene may contain a relatively small amount of residual A atoms, for example, 10 mass % or less of the original A atoms. The amount of residual A atoms may be preferably 8 mass % or less, more preferably 6 mass % or less. However, even if the amount of residual A atoms exceeds 10 mass %, there may be cases where there is no problem depending on the application and use conditions of the paste (and the conductive film obtained thereby).

[0027] The MXene (particle) 10 thus synthesized may be a layered material comprising one or more MXene layers 7a, 7b, as shown diagrammatically in FIG. 2 (examples of MXene (particle) 10 include, but are not limited to, one layer of MXene 10a in FIG. 2(a) and two layers of MXene 10b in FIG. 2(b)). More specifically, the MXene layers 7a, 7b may be formed of M m X n The layer body (M m X n The MXene layers 7a and 7b have the following structures: (1) a, 1b of the layer bodies 1a and 1b; and (2) modifications or terminations T3a, 5a, 3b, 5b present on the surfaces of the layer bodies 1a and 1b (more specifically, on at least one of the two surfaces facing each other in each layer). m X n T x ", where x is any number. MXene10 may be one in which such MXene layers are individually separated and exist as one layer (single layer structure shown in FIG. 2(a), so-called single layer MXene10a), a laminate in which a plurality of MXene layers are stacked at a distance from each other (multilayer structure shown in FIG. 2(b), so-called multilayer MXene10b), or a mixture thereof. MXene10 may be a particle (which may also be called a powder or flake) as an aggregate composed of single layer MXene10a and / or multilayer MXene10b. In this embodiment, MXene10 is preferably a particle (which may also be called a nanosheet) the majority of which is composed of single layer MXene10a. In the case of multilayer MXene, two adjacent MXene layers (e.g. 7a and 7b) do not necessarily have to be completely separated and may be partially in contact with each other. Even when the multilayer MXene is included, it is preferable that the multilayer MXene is an MXene with a small number of layers obtained through a delamination process. The term "few layers" as used herein means that the number of stacked layers of MXene is, for example, 10 or less. Hereinafter, this "multilayer MXene with a few layers" may be referred to as "few-layer MXene." The thickness of the few-layer MXene in the stacking direction is preferably 10 nm or less. In this specification, the single-layer MXene and few-layer MXene may be collectively referred to as "single-layer / few-layer MXene."

[0028] Without being limiting to this embodiment, the thickness of each MXene layer (corresponding to the above-mentioned MXene layers 7a and 7b) is, for example, 0.8 nm to 5 nm, particularly 0.8 nm to 3 nm (which can vary mainly depending on the number of M atomic layers contained in each layer), and the maximum dimension in a plane parallel to the layer (two-dimensional sheet surface) is, for example, 0.1 μm to 200 μm, particularly 1 μm to 40 μm. When the MXene is a laminate (multilayer MXene), for each laminate, the interlayer distance (or gap dimension, shown as Δd in Figure 2(b)) is, for example, 0.8 nm or more and 10 nm or less, particularly 0.8 nm or more and 5 nm or less, more particularly about 1 nm; the total number of layers may be 2 or more, but is, for example, 50 to 100,000, particularly 1,000 to 20,000; the thickness in the stacking direction is, for example, 0.1 μm to 200 μm, particularly 1 μm to 40 μm; and the maximum dimension in a plane perpendicular to the stacking direction (two-dimensional sheet surface) is, for example, 0.1 μm to 100 μm, particularly 1 μm to 20 μm. These dimensions are determined as number-average dimensions (e.g., number-average of at least 40 particles) based on scanning electron microscope (SEM), transmission electron microscope (TEM) or atomic force microscope (AFM) photographs, or as distances in real space calculated from the position in reciprocal space of the (002) plane measured by X-ray diffraction (XRD).

[0029] In this embodiment, the polymer material to be mixed with the particles of the layered material has at least one hydrogen acceptor selected from the group consisting of fluorine atoms, chlorine atoms, oxygen atoms and nitrogen atoms, and has a hydroxyl group and / or a secondary amino group as a hydrogen donor.

[0030] This embodiment will be described with reference to Figs. 3(a) to (c), which are schematic diagrams illustrating the presence or absence of hydrogen bonds in a conductive composite material. 3 C 2 T xIn the past, as shown in FIG. 3(a), the presence of a polymer material would cause a repulsive force between MXene and the polymer material, increasing the interplanar distance between MXene molecules, which would lead to a decrease in electrical conductivity due to the presence of the polymer material. In contrast, according to the present embodiment, as described above, the polymer material has a hydrogen acceptor and a hydrogen donor, and as shown in FIG. 3(b) and FIG. 3(c), hydrogen bonds (shown by dashed lines in FIG. 3(b) and FIG. 3(c)) are formed between the MXene surface and the polymer material. In particular, as shown in FIG. 3(c), the polymer material has both a hydrogen acceptor and a hydrogen donor, and therefore more hydrogen bonds can be formed between the MXene surface and the polymer material than in the past. As a result, the interplanar distance between MXene molecules can be reduced, and it is believed that high electrical conductivity can be achieved while increasing the film strength. More specifically, since MXene always has at least one type selected from the group consisting of hydroxyl, fluorine, chlorine, oxygen and hydrogen atoms as a terminal group, if the polymer material has at least one type selected from the group consisting of fluorine, chlorine, oxygen and nitrogen atoms as a hydrogen acceptor and a hydroxyl and / or secondary amino group as a hydrogen donor, the interplanar distance between MXene molecules can be reduced by hydrogen bonds between MXene and the polymer material, and high conductivity can be achieved while increasing film strength. In addition to the hydrogen bonds, the Ti-N and CN bonds formed between them are thought to contribute to the improved affinity between MXene and the polymer material.

[0031] The polymer material comprises: One or more of a polymer having a urethane bond and a polymer having a unit derived from a (meth)acryloyl group, or Combination of one or more of these polymers with an additive having one or more of a hydroxyl group and a secondary amino group. It is preferred that the compound has the formula:

[0032] Examples of polymers constituting the above polymer materials include polyethyleneimine (PEI), polypyrrole (PPy), polyaniline (PANI), polyimides (PI) containing secondary amino groups such as flame-retardant polyimides, and polymer species having a urethane bond (-NHCO-), such as polyamideimide (PAI), polyacrylamide (PMA), nylon (polyamide resin), DNA (deoxyribonucleic acid), acetanilide, and acetaminophen.

[0033] Among these, as the polymer constituting the polymer material, as described above, one or more of a polymer having a urethane bond and a polymer having a unit derived from a (meth)acryloyl group are preferred. The polymer having a urethane bond and the polymer having a unit derived from a (meth)acryloyl group have high affinity with the MXene, can form a smooth film, and contribute to improving the conductivity. As a result, both higher conductivity and high strength can be achieved. The polymer material is preferably composed of one or more of a polymer having a urethane bond and a polymer having a unit derived from a (meth)acryloyl group, and more preferably composed of a polymer having a urethane bond.

[0034] The polymer having the urethane bond is more preferably polyurethane, and more preferably one or more of polyether polyurethane, polycarbonate polyurethane, and polyester polyurethane. Polyether polyurethane means polyurethane containing structural units derived from polyester, polycarbonate polyurethane means polyurethane containing structural units derived from polycarbonate, and polyester polyurethane means polyurethane containing structural units derived from polyester. The polymer material is more preferably composed of one or more of polyether polyurethane, polycarbonate polyurethane, and polyester polyurethane.

[0035] A polymer having a unit derived from a (meth)acryloyl group, i.e., an acrylic resin, is a polymer having a structural unit derived from one or more of acrylic acid and methacrylic acid. The acrylic resin is more preferably an anionic acrylic resin. More preferably, the anionic acrylic resin has one or more of an alkoxymethylamide group and a hydroxyl group.

[0036] In another embodiment, the polymer material may include a combination of the polymer and an additive having one or more of a hydroxyl group and a secondary amino group. The additive having one or more of a hydroxyl group and a secondary amino group may be a surfactant having one or more of a hydroxyl group and a secondary amino group. An example of the surfactant is tetraethylene glycol. When the polymer material includes the additive, the additive may be a hydrogen donor in addition to the polymer. For example, the polymer material may be a combination of a polymer having a unit derived from a (meth)acryloyl group and a surfactant such as tetraethylene glycol.

[0037] The ratio of the particles of the layered material is more than 19 volume % and 95 volume % or less. By making the ratio of the particles of the layered material more than 19 volume %, electrical conductivity can be ensured. From the viewpoint of further increasing electrical conductivity, the ratio of the particles of the layered material is more preferably 30 volume % or more, even more preferably 35 volume % or more, and even more preferably 50 volume % or more. On the other hand, from the viewpoint of ensuring the film strength of the composite material of MXene particles / polymer material, the ratio of the particles of the layered material is preferably 95 volume % or less, more preferably 75 volume % or less, and even more preferably 50 volume % or less. The ratio of the particles of the layered material refers to the ratio in the conductive composite material. The conductive composite material of the present invention may contain additives such as colorants and antioxidants, and in this case, the ratio of the particles of the layered material refers to the ratio in the conductive composite material including the additives.

[0038] The conductive composite material of the present embodiment may have any shape. For example, it may be a planar shape (sheet shape), a rectangular parallelepiped, a sphere, a polygonal shape, or a paste, a slurry, or the like. The conductive composite material of the present embodiment may be a coating film formed on the surface of a substrate. When the conductive composite material of the present embodiment is a coating film, it is not limited to a planar shape (sheet shape), and may be attached to at least a part of the surface of the object to be coated or cover the object to be coated according to the shape of the object. A preferred form of the shape of the conductive composite material is a planar shape (sheet shape). When it is a planar shape (sheet shape), it may have two main surfaces facing each other. The thickness of the sheet-shaped conductive composite material, and the shape and dimensions when viewed from above may be appropriately selected depending on the application of the conductive composite material. The conductive composite material of the present embodiment may be a paste such as a conductive paste, or a slurry. Examples of the paste or slurry include a mixture of particles of a predetermined layered material and a polymer material, and further, if necessary, an aqueous medium liquid, an organic medium liquid, metal particles, ceramic particles, or the like. The mass ratio of the particles of the layered material in the paste or slurry is, for example, 20% or more, and further 50% or more. An example of the application of the paste or slurry is to apply the paste or slurry to a substrate or the like and dry it to form a conductive film.

[0039] When the conductive composite material of the present embodiment is formed on the surface of a substrate, the shape and material of the substrate are not particularly limited. The shape of the substrate can be, for example, plate-like, spherical, needle-like, or uneven. The material of the substrate can be a metal material, a ceramic material, a polymer material containing a conductive polymer, or a composite material of two or more of these. For example, the metal material can be gold, silver, copper, platinum, nickel, titanium, tin, iron, zinc, magnesium, aluminum, tungsten, molybdenum, or an alloy containing 50 mass % or more of these metals.

[0040] When the conductive composite material is in the form of a sheet, its thickness can be measured by observing a cross section using, for example, a micrometer, a stylus-type surface profiler, a scanning electron microscope (SEM), a microscope, a laser microscope, or the like.

[0041] The method for producing the conductive composite material of the present embodiment using the MXene produced as described above is not particularly limited. When the conductive composite material of the present embodiment has a sheet-like form, for example, as shown in the following example, the layered material and the polymer material can be mixed to form a coating film.

[0042] First, an MXene aqueous dispersion or an MXene organic solvent dispersion, or an MXene powder, in which the MXene particles (particles of a layered material) are present in a solvent, is mixed with a polymer material. The solvent of the MXene aqueous dispersion is typically water, and in some cases, it may contain a relatively small amount of other liquid substance in addition to water (for example, 30 mass % or less, preferably 20 mass % or less on a total basis).

[0043] The MXene particles and polymer material can be stirred using a dispersing device such as a homogenizer, a propeller stirrer, a thin film rotary stirrer, a planetary mixer, a mechanical shaker, or a vortex mixer.

[0044] The slurry, which is a mixture of the MXene particles and the polymer material, may be applied to an object such as a substrate, but the application method is not limited. For example, there may be a spray application method using a nozzle such as a one-fluid nozzle, a two-fluid nozzle, or an airbrush, a slit coating method using a table coater, a comma coater, or a bar coater, a screen printing method, a metal mask printing method, a spin coating method, or a drop application method. The object may be a printed circuit board, a metal board, a resin board, a laminated electronic component, a metal pin, a metal wire, or the like, as appropriate, depending on the application.

[0045] The above coating and drying steps may be repeated several times as necessary until a film of the desired thickness is obtained. Drying and curing may be performed at a temperature of 400° C. or less using, for example, an atmospheric oven or a vacuum oven.

[0046] As shown in the examples described later, the conductive composite material of this embodiment preferably maintains a conductivity of 280 S / cm or more when it is in the form of a sheet having a thickness of, for example, 5 μm. The conductivity can be preferably maintained at 1000 S / cm or more, more preferably 2000 S / cm or more, even more preferably 3000 S / cm or more, and even more preferably 6000 S / cm or more. There is no particular upper limit to the conductivity of the conductive film, but it can be, for example, 25000 S / cm or less. The conductivity can be measured using a resistivity meter.

[0047] Since the conductive composite material of the present embodiment has high electrical conductivity and high strength as described above, it can be used in any suitable application, such as an electrode in any suitable electric device, an electromagnetic shield (EMI shield), etc., which require high electrical conductivity to be maintained (reducing the decrease in initial electrical conductivity and preventing oxidation).

[0048] Although the conductive composite material according to one embodiment of the present invention has been described above in detail, various modifications are possible. Note that the conductive composite material according to the present invention may be produced by a method different from the production method according to the above embodiment. EXAMPLES

[0049] [Example 1] Preparation of MAX particles (precursor of MXene particles) TiC powder, Ti powder, and Al powder (all manufactured by Kojundo Chemical Laboratory Co., Ltd.) were mixed in a molar ratio of 2:1:1 in a ball mill containing zirconia balls for 24 hours. The mixed powder was sintered at 1350°C for 2 hours in an Ar atmosphere. The sintered body (block) thus obtained was pulverized with an end mill to a maximum dimension of 40 μm or less. As a result, TiC powder was obtained as the MAX particle. 3AlC 2 particles were obtained.

[0050] Precursor etching and Li intercalation Ti prepared by the above method 3 AlC 2 Using particles (powder), etching and Li intercalation were performed under the following etching conditions. 3 AlC 2 A solid-liquid mixture (slurry) containing solid components derived from the powder was obtained. (Precursor etching and Li intercalation conditions) Precursor: Ti 3 AlC 2 (Through a 45μm sieve) Etching solution composition: LiF 3g HCl (9M) 30mL Precursor input: 3g Etching container: 100mL Eyeboy Etching temperature: 35℃ Etching time: 24h Stirrer speed: 400 rpm

[0051] Post-etch cleaning The above slurry was divided into two portions and placed in two 50 mL centrifuge tubes, and centrifuged at 3500 G using a centrifuge, after which the supernatant was discarded. (i) 40 mL of pure water was added to the remaining precipitate in each centrifuge tube, (ii) centrifuged again at 3500 G, and (iii) the supernatant was separated and removed. These steps (i) to (iii) were repeated a total of 10 times, and after confirming that the pH of the 10th supernatant was greater than 5, the supernatant was discarded and Ti 3 C 2 T x - Moisture medium clay was obtained.

[0052] Delamination The above Ti 3 C 2 T x(i) 40 mL of pure water was added to the aqueous medium clay, which was then stirred on a shaker for 15 minutes, (ii) centrifuged at 3500G, and (iii) the supernatant was collected as a single-layer MXene-containing solution. These steps (i) to (iii) were repeated a total of four times to obtain a single-layer MXene-containing supernatant. This supernatant was then centrifuged at 4300G for two hours using a centrifuge, after which the supernatant was discarded and single-layer and single-layer MXene-containing clay was obtained as a single-layer and single-layer MXene-containing sample.

[0053] Formation of MXene / polyurethane composite membrane MXene(Ti) in MXene / polyurethane composite membranes 3 C 2 T x The above single-layer and few-layer MXene-containing clays, pure water, and polyurethane (Rezamin D-4080 (polyether / carbonate type) manufactured by Dainichi Seika Chemicals Mfg. Co., Ltd.) were mixed so that MXene / polyurethane composite films with MXene / polyurethane composite film ratios (after film formation and drying) of 25, 50, 75, and 100 volume %, respectively, were obtained, and the mixture was manually stirred for 5 minutes to obtain an MXene / polyurethane composite liquid.

[0054] The obtained MXene / polyurethane composite liquid was spray-coated onto a PET substrate (Lumirror (registered trademark) manufactured by Toray Industries, Inc., 15 cm square). The above spray irradiation and drying with a dryer were repeated 15 times until the film thickness of the MXene / polyurethane composite reached 5 μm. After coating, the film was dried in a normal pressure oven at 80°C for about 30 minutes to obtain an MXene / polyurethane composite film.

[0055] [Example 2] Preparation of MAX particles (precursor of MXene particles) MAX particles were obtained in the same manner as in Example 1.

[0056] Etching of precursors Ti prepared by the above method 3 AlC 2 Etching was performed using particles (powder) under the following etching conditions. 3 AlC2 A solid-liquid mixture (slurry) containing solid components derived from the powder was obtained. (Etching conditions) Precursor: Ti 3 AlC 2 (Through a 45μm sieve) Etching solution composition: 49% HF 6mL H 2 O 18mL HCl (12M) 36mL Precursor input: 3.0g Etching container: 100mL Eyeboy Etching temperature: 35℃ Etching time: 24h Stirrer speed: 400 rpm

[0057] Post-etch cleaning The slurry was divided into two and placed in two 50 mL centrifuge tubes, respectively, and centrifuged at 3500 G using a centrifuge, after which the supernatant was discarded. 40 mL of pure water was added to the remaining precipitate in each centrifuge tube, and the tubes were centrifuged again at 3500 G to separate and remove the supernatant. This operation was repeated 11 times. After the final centrifugation, the supernatant was discarded, and Ti 3 C 2 T x - Moisture medium clay was obtained.

[0058] Lithium intercalation Ti prepared by the above method 3 C 2 T x -Li intercalation was carried out on the water medium clay by using LiCl as the Li-containing compound and stirring for 12 hours at 20°C to 25°C under the following conditions. (Li intercalation conditions) ·Ti 3 C 2 T x - Moisture medium clay (MXene after washing): 0.75g solids LiCl: 0.75g Intercalation vessel: 100mL Eye Boy ·Temperature: 20℃ or higher and 25℃ or lower (room temperature) ·Time: 10h Stirrer speed: 800 rpm

[0059] Delamination The above Ti 3 C 2 T x (i) 40 mL of pure water was added to the aqueous medium clay, which was then stirred on a shaker for 15 minutes, (ii) centrifuged at 3500G, and (iii) the supernatant was collected as a single-layer MXene-containing solution. These steps (i) to (iii) were repeated a total of four times to obtain a single-layer MXene-containing supernatant. This supernatant was then centrifuged at 4300G for two hours using a centrifuge, after which the supernatant was discarded and single-layer and single-layer MXene-containing clay was obtained as a single-layer and single-layer MXene-containing sample.

[0060] Formation of MXene / acrylic composite film MXene(Ti) in MXene / acrylic composite film 3 C 2 T x The above single-layer and few-layer MXene-containing clays, pure water, and acrylic resin (NW-400, manufactured by Toagosei Co., Ltd., hereafter referred to as "acrylic") were mixed so as to obtain an MXene / acrylic composite film with a volume ratio (after film formation and drying) of 25 and 83%, respectively, and the mixture was stirred for 15 minutes with a shaker (SK550 1.1, manufactured by FAST & Fluid) to obtain an MXene / acrylic composite liquid.

[0061] The obtained MXene / acrylic composite material liquid was spray-coated onto a PI substrate (3 cm square, manufactured by AS ONE Corporation). The above spray coating and drying with a dryer were repeated 30 times to form a coating film before drying. After coating, the substrate was dried in a normal pressure oven at 80°C for 2 hours and then in a vacuum oven at 150°C for about 15 hours to obtain an MXene / acrylic composite material film.

[0062] [Comparative Example 1] Sodium alginate (SA) was used as the polymer material, and the MXene (Ti) in the MXene / sodium alginate (SA) composite membrane was 3 C 2 T x MXene / SA composite membranes were obtained in the same manner as in Example 1 above, except that the MXene / SA composite membranes had a MXene / SA composite membrane ratio (after film formation and drying) of 3, 12, 24, 32, 55, 73, or 100 volume %, respectively.

[0063] [Comparative Example 2] Polyvinyl alcohol (PVA) was used as the polymer material, and MXene (Ti) in MXene / PVA composite membranes was 3 C 2 T x MXene / PVA composite films were obtained in the same manner as in Example 1 above, except that the MXene / PVA composite films had a MXene / PVA composite film ratio (after film formation and drying) of 1, 13, 26, 48, 67, and 100 volume %, respectively.

[0064] [Measurement of electrical conductivity of composite film] The electrical conductivity of the obtained MXene / polyurethane composite film, MXene / acrylic composite film, MXene / SA composite film, and MXene / PVA composite film was determined. The electrical conductivity was calculated by measuring the resistivity (Ω) and thickness (μm) at three points per sample, calculating the electrical conductivity (S / cm) from these measurements, and using the arithmetic average of the three electrical conductivities obtained. A low resistivity meter (Loresta AX MCP-T370, manufactured by Mitsubishi Chemical Analytical Co., Ltd.) was used to measure the resistivity. A micrometer (MDH-25MB, manufactured by Mitutoyo Co., Ltd.) was used to measure the thickness. The results are shown in Figure 4. In Figure 4, the electrical conductivity of the MXene film alone differs depending on the difference in the MXene preparation method, the presence or absence and content of impurities contained in the obtained composite film, etc. Therefore, the percentage of the electrical conductivity of each MXene content was also determined for each composite film in Figure 4, assuming that the electrical conductivity when the MXene content is 100% by volume (i.e., the polymer material is 0% by volume) is 100%. The results are shown in Figure 5. In Figures 4 and 5, the MXene content indicates the proportion (volume %) of MXene in the composite material film after film formation and drying.

[0065] In the case of the MXene / polyurethane composite membrane, as shown in Fig. 4, MXene(Ti 3 C 2 T x When the ratio of Ti) was 75 volume %, the conductivity was about 4600 S / cm. This conductivity was about 4600 S / cm when the ratio of Ti) was 75 volume %. 3 C 2 T x This corresponds to 68% of the conductivity of 100% by volume. 3 C 2 T x Even when the ratio of Ti was as small as 25 vol%, pure MXene (i.e., Ti 3 C 2 T x It was possible to secure 15% of the electrical conductivity of 100% by volume. 3 C 2 T x When the proportion of 19% by volume, a conductivity of approximately 280 S / cm was achieved.

[0066] In the case of the MXene / acrylic composite film, as shown in Figure 4, MXene(Ti 3 C 2 T x When the ratio of Ti) was 83 volume %, the conductivity was about 15000 S / cm. This conductivity was about 15000 S / cm when the ratio of Ti) was 83 volume %. 3 C 2 T x This corresponds to 79% of the conductivity of 100% by volume. 3 C 2 T x Even when the ratio of Ti was as small as 25 vol%, pure MXene (i.e., Ti 3 C 2 T x The conductivity was 18% of that of 100% by volume.

[0067] On the other hand, in the case of the MXene / PVA composite membrane, as shown in Figs. 4 and 5, MXene(Ti 3 C 2 T x Even when the ratio of Ti was as high as 67 volume %, the electrical conductivity was low at 220 S / cm. 3 C 2 T x The electrical conductivity decreased to less than 10% of the 100% by volume electrical conductivity.

[0068] In contrast, the conductivity of the MXene / PVA composite film was significantly lower, while the MXene / SA composite film maintained its conductivity, but as shown in Table 2 below, the film strength was low and cohesive failure was observed at all SA contents.

[0069] [Strength evaluation of composite membranes] After the electrical conductivity measurements, a tape peeling test was performed on each of the MXene / polyurethane composite film, MXene / acrylic composite film, and MXene / SA composite film as follows. In detail, an adhesive tape (SCOTCH 600TAPE, 1 / 2 inch wide, manufactured by 3M) was applied to a part of the upper surface of the composite film formed on the PET substrate, and then peeled off to visually check for cohesive failure of the composite film, i.e., the presence or absence of intra-film separation due to transfer of a part of the composite film to the adhesive surface of the tape. The evaluation results for the cases where polyurethane, acrylic, and SA were used as the polymer material are shown in Tables 1, 2, and 3, respectively.

[0070] [Table 1]

[0071] [Table 2]

[0072] [Table 3]

[0073] The results in Tables 1, 2, and 3 confirm that in the case of the MXene film alone, the film adhered to both the peeled adhesive tape and the substrate, and cohesive failure (fracture within the film) had occurred. Furthermore, when SA was used as the polymer material, cohesive failure occurred, just like in the MXene film alone, regardless of the MXene content. On the other hand, no cohesive failure occurred in samples in which polyurethane or acrylic was mixed as the polymer material.

[0074] From the results of the measurements of the electrical conductivity and strength of the composite material film, in this embodiment, the composite material of MXene particles and polymer material can ensure electrical conductivity and high strength by adding a predetermined amount of MXene particles. In particular, it can be estimated that the electrical conductivity of about 280 S / cm or more can be obtained by making the ratio of the layered material (MXene) more than 19% by volume. In particular, the electrical conductivity of the composite material containing 75% by volume of MXene together with polyurethane was 68% of the electrical conductivity of the pure MXene film. In addition, the electrical conductivity of the composite material containing 83% by volume of MXene together with acrylic was 79% of the electrical conductivity of the pure MXene film. The reason why both the high electrical conductivity and the high strength were achieved is thought to be that, as mentioned above, the hydrogen bonds between the MXene and the polymer material reduced the interplanar spacing, and a state in which electricity easily flows was maintained. Note that acrylic acid, which is the raw material of the acrylic used in the examples, has carboxyl groups (hydroxyl groups), and some carboxyl groups remain even after synthesis, that is, it is thought that the acrylic has a certain number of hydroxyl groups. The disclosure of this specification may include the following aspects. (Aspect 1) 1. A conductive composite material comprising particles of a layered material comprising one or more layers and a polymeric material, The layer comprises a compound having the following formula: M m X n (wherein M is at least one Group 3, 4, 5, 6, or 7 metal; X is a carbon atom, a nitrogen atom, or a combination thereof; n is 1 to 4, m is greater than n and less than or equal to 5) and a modification or termination T (T is at least one selected from the group consisting of a hydroxyl group, a fluorine atom, a chlorine atom, an oxygen atom, and a hydrogen atom) present on the surface of the layer body, The polymeric material comprises: at least one hydrogen acceptor selected from the group consisting of a fluorine atom, a chlorine atom, an oxygen atom, and a nitrogen atom; and having a hydroxyl group and / or a secondary amino group as a hydrogen donor; 13. A conductive composite material, wherein the proportion of particles of said layered material is greater than 19% by volume and not greater than 95% by volume. (Aspect 2) The modification or terminal T is At least one hydrogen acceptor selected from the group consisting of a fluorine atom, a chlorine atom, and an oxygen atom; and 2. The conductive composite material according to embodiment 1, having hydroxyl groups and / or hydrogen atoms as hydrogen donors. (Aspect 3) The polymer material comprises: One or more of a polymer having a urethane bond and a polymer having a unit derived from a (meth)acryloyl group, or Combination of one or more of these polymers with an additive having one or more of a hydroxyl group and a secondary amino group. 3. The conductive composite material of embodiment 1 or 2, having the following structure: (Aspect 4) The conductive composite material according to any one of aspects 1 to 3, wherein M is at least one selected from the group consisting of Ti, Zr, Hf, V, Nb, Ta, Cr, Mo, and Mn. (Aspect 5) The layer body is Ti 3 C 2 , Ti 3 CN, and Ti 2 The conductive composite material according to any one of aspects 1 to 4, comprising at least one selected from the group consisting of C. (Aspect 6) 6. The conductive composite material according to any one of aspects 1 to 5, wherein the polymer material is one or more of a polyether-based polyurethane, a polycarbonate-based polyurethane, and a polyester-based polyurethane. (Aspect 7) The conductive composite material according to any one of embodiments 1 to 6, which has the form of a coating film. (Aspect 8) The conductive composite material according to any one of aspects 1 to 7, having a conductivity of 280 S / cm or more. [Industrial Applicability]

[0075] The conductive composite material of the present invention can be used for any suitable purpose, and can be preferably used, for example, as an electrode or electromagnetic shield in an electric device.

[0076] This application claims priority from Japanese Patent Application No. 2020-131866, which is incorporated herein by reference. [Explanation of symbols]

[0077] 1a, 1b layer body (M m X n layer) 3a, 5a, 3b, 5b Modified or terminal T 7a, 7b MXene layers 10, 10a, 10b MXene particles (particles of layered materials) 11 Polymer Materials 20 Conductive composite materials

Claims

1. A conductive composite material for use in an electrode, comprising particles of a layered material comprising a plurality of layers and a polymeric material, the composite comprising: The layer has the following formula: M m X n wherein M is at least one Group 3, 4, 5, 6, or 7 metal; X is a carbon atom, a nitrogen atom, or a combination thereof; n is 1 or more and 4 or less, m is greater than n and is equal to or less than 5. and a modification or terminal T (T is at least one selected from the group consisting of a hydroxyl group, a fluorine atom, a chlorine atom, an oxygen atom, and a hydrogen atom) present on the surface of the layer body, the interlayer distance of the plurality of layers is 0.8 nm or more and 10 nm or less; The polymeric material comprises: A polymer having units derived from a (meth)acryloyl group, at least one hydrogen acceptor selected from the group consisting of a fluorine atom, a chlorine atom, an oxygen atom, and a nitrogen atom; and having a hydroxyl group and / or a secondary amino group as a hydrogen donor; the proportion of particles of said layered material is greater than 19% by volume and less than or equal to 95% by volume; A conductive composite material having a conductivity of 280 S / cm or more.

2. The modification or terminal T is At least one hydrogen acceptor selected from the group consisting of a fluorine atom, a chlorine atom, and an oxygen atom; and The conductive composite material according to claim 1 , which has hydroxyl groups and / or hydrogen atoms as hydrogen donors.

3. The polymer material comprises: A polymer having a urethane bond, or an additive having one or more of a hydroxyl group and a secondary amino group, or A combination of a polymer having a urethane bond and an additive having at least one of a hydroxyl group and a secondary amino group. The conductive composite material according to claim 1 or 2, having the following structure:

4. A conductive composite material for use in an electrode, comprising particles of a layered material comprising a plurality of layers and a polymeric material, the composite comprising: The layer has the following formula: M m X n wherein M is at least one Group 3, 4, 5, 6, or 7 metal; X is a carbon atom, a nitrogen atom, or a combination thereof; n is 1 or more and 4 or less, m is greater than n and is equal to or less than 5. and a modification or terminal T (T is at least one selected from the group consisting of a hydroxyl group, a fluorine atom, a chlorine atom, an oxygen atom, and a hydrogen atom) present on the surface of the layer body, the interlayer distance of the plurality of layers is 0.8 nm or more and 10 nm or less; The polymeric material comprises: one or more of a polymer having a urethane bond and a polymer having a unit derived from a (meth)acryloyl group, or Combination of one or more of these polymers with an additive having one or more of a hydroxyl group and a secondary amino group. having at least one hydrogen acceptor selected from the group consisting of a fluorine atom, a chlorine atom, an oxygen atom, and a nitrogen atom; and having a hydroxyl group and / or a secondary amino group as a hydrogen donor; the proportion of particles of said layered material is greater than 19% by volume and less than or equal to 95% by volume; A conductive composite material having a conductivity of 280 S / cm or more.

5. A conductive composite material for use in an electrode, comprising particles of a layered material comprising a plurality of layers and a polymeric material, the composite comprising: The layer has the following formula: M m X n wherein M is at least one Group 3, 4, 5, 6, or 7 metal; X is a carbon atom, a nitrogen atom, or a combination thereof; n is 1 or more and 4 or less, m is greater than n and is equal to or less than 5. and a modification or terminal T (T is at least one selected from the group consisting of a hydroxyl group, a fluorine atom, a chlorine atom, an oxygen atom, and a hydrogen atom) present on the surface of the layer body, the interlayer distance of the plurality of layers is 0.8 nm or more and 10 nm or less; The polymeric material comprises: one or more of polyethyleneimine, polypyrrole, polyaniline, polyimide containing secondary amino groups, polyamideimide, polyacrylamide, nylon, DNA (deoxyribonucleic acid), acetanilide, and acetaminophen; at least one hydrogen acceptor selected from the group consisting of a fluorine atom, a chlorine atom, an oxygen atom, and a nitrogen atom; and having a hydroxyl group and / or a secondary amino group as a hydrogen donor; the proportion of particles of said layered material is greater than 19% by volume and less than or equal to 95% by volume; A conductive composite material having a conductivity of 280 S / cm or more.

6. The conductive composite material according to any one of claims 1 to 5, wherein M is at least one selected from the group consisting of Ti, Zr, Hf, V, Nb, Ta, Cr, Mo and Mn.

7. The layer body is Ti 3 C 2 , Ti 3 CN, and Ti 2 The conductive composite material according to any one of claims 1 to 6, comprising at least one selected from the group consisting of C.

8. The conductive composite material according to any one of claims 1 to 7, which has the form of a coating film.

Citation Information

Patent Citations

  • Waterborne polyurethane-MXene electromagnetic shielding bionic nanocomposite material film and preparation method

    CN110698847A

  • Preparation and application of electromagnetic shielding coating layer based on MXene two-dimensional material

    CN111171703A

  • Implantable devices using 2d metal carbides and nitrides (mxenes)

    WO2019055784A1